2014
DOI: 10.1016/j.molcel.2014.04.032
|View full text |Cite
|
Sign up to set email alerts
|

The Histone Deacetylases Sir2 and Rpd3 Act on Ribosomal DNA to Control the Replication Program in Budding Yeast

Abstract: In S. cerevisiae, replication timing is controlled by epigenetic mechanisms restricting the accessibility of origins to limiting initiation factors. About 30% of these origins are located within repetitive DNA sequences such as the ribosomal DNA (rDNA) array, but their regulation is poorly understood. Here, we have investigated how histone deacetylases (HDACs) control the replication program in budding yeast. This analysis revealed that two HDACs, Rpd3 and Sir2, control replication timing in an opposite manner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
103
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(122 citation statements)
references
References 43 publications
16
103
3
Order By: Relevance
“…Alternatively, the hyopacetylation of H4K16 in these regions could be due to transient Sir2 association not captured by ChIP-Seq. Previous studies have shown that Sir2, but not Sir3 or Sir4, controls some origins of replication (Pappas et al 2004;Crampton et al 2008;Yoshida et al 2014). However, MACS did not detect any significant enrichment for Sir2 at subtelomeric ARSs outside the core X element.…”
Section: Catalytic Activity Of Sir2 At Telomerescontrasting
confidence: 54%
“…Alternatively, the hyopacetylation of H4K16 in these regions could be due to transient Sir2 association not captured by ChIP-Seq. Previous studies have shown that Sir2, but not Sir3 or Sir4, controls some origins of replication (Pappas et al 2004;Crampton et al 2008;Yoshida et al 2014). However, MACS did not detect any significant enrichment for Sir2 at subtelomeric ARSs outside the core X element.…”
Section: Catalytic Activity Of Sir2 At Telomerescontrasting
confidence: 54%
“…origin efficiency at other loci (11,12). Overall, these observations suggest that increased replication of repetitive regions of the genome can lead to replication gaps elsewhere, and that the presence of such gaps may constitute the proximal cause of death in cellular aging.…”
Section: Significancementioning
confidence: 85%
“…This effect is regulated by Rif1-dependent recruitment of protein phosphatase I, which may antagonize origin activation by the cyclin-and DBF4-dependent kinases (Lian et al 2011;Davé et al 2014;Hiraga et al 2014;Mattarocci et al 2014). Chromatin structure-in particular, histone deacetylation by Sir2 and Rpd3-also affects the timing of nontelomeric origins (Knott et al 2009(Knott et al , 2012Peace et al 2014;Yoshida et al 2014). However, the effect of chromatin structure on euchromatic origins is much weaker, and its mechanism is unclear.…”
mentioning
confidence: 99%